Localized periodontitis severity associated with carotid intima-media thickness in young adults: CHIEF atherosclerosis study - Kun-Zhe Tsai; Wei-Chun Huang; Yun-Chen Chang; Younghoon Kwon; Xuemei Sui; Carl J. Lavie; Gen-Min Lin (Scientific Reports, 2023)
Abstract This study aimed to investigate the association of periodontitis with subclinical atherosclerosis in young adults. In total, 486 non-diabetic military personnel were included in Taiwan. Carotid intima-media thickness (cIMT) was assessed utilizing sonography for subclinical atherosclerosis. Periodontitis severity was defined based on the 2017 US/European consensus. Mean cIMT was compared by analysis of covariance (ANCOVA), and multiple logistic regression model was used to determine the association of periodontitis severity and the highest quintile of cIMT (≥ 0.8 mm) with adjustments for age, sex, metabolic risk factors and leukocyte counts. The mean cIMT increased in those with greater stages (periodontal health (N = 349): 0.65 mm, Stage I (N = 41): 0.72 mm, Stage II (N = 57): 0.74 mm and Stage III: 0.76 mm, respectively, p < 0.01). In multiple logistic regression, a dose–response association from Stage I to Stage III periodontitis for cIMT ≥ 0.8 mm was also found [ORs and 95% CIs 1.41 (0.60–3.29), 1.62 (0.79–3.31) and 3.20 (1.42–7.18)]. Leucocyte counts ≥ 7.6 × 103/µL (the highest quintile) was associated with cIMT ≥ 0.8 mm [OR 1.86 (1.11–3.12)], while no association existed for other metabolic risk factors. In conclusion, severe periodontitis and leukocyte counts are independent risk factors of increased cIMT, emphasizing the critical role of inflammation in subclinical atherosclerosis.